THE EFFECT OF CURRENT RATIO, MANAGERIAL OWNERSHIP, ASSET GROWTH AND THE SIZE OF FUNDING POLICY IN REAL ESTATE & PROPERTY COMPANY LISTED IN 2009-2012 PERIOD - Sari, Mia Permata; Ratnawati, Vince; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to see the effect of the current ratio, managerial ownership, asset growth, and the company size on the funding policy.The population of this research are all companies include in the group of Real Eatate & Property which go public on the Indonesia Stock Exchange in 2012as many as 51 companies. The companies that fulfill the critera and be the sample are 32 companies. The research analysis which is used was multiple linear regression equation with yhe help of SPSS software ( Statistical Product and Service Solution ).The results showed that the current ratio was proven to affect the funding policy on the Real Estate & Property Company. It can be seen from the t-test (3.360)> -table (1.980)and p-value (0.001)< α (0.05), meaning that the greater value of the current ratiogive and inpact on funding policies value of the companies concerned. Managerial Ownership showed that it has no effect on funding policies on Real Estate & Property Company. It can be seen from the t-test(2.756)> t-table (1.980) and p value (0.007)< α (0.05), meaning that the changes in managerial ownership will not give an effect on funding policy value on company concerned. Asset growth proved that there is no effect on the funding policy of the real estate & property company. It can be seen from t-test (-1.661) <t-table (1.980) and p value(0.099)> α (0.05), meaning that changes in growth asset will not affect the value of the policy round of funding in the company concerned. But it was showed that the size of the company affect of the funding policy of the real estate financing and property company. It can be seen from the t-test (4.909)> t-table (1.980) and p value (0.000)< α (0.05), meaning that changes in the value of the size of the company will have an impact on the value of the funding policies of the companies concerned. The coefficient of determination is 0.208 which showed that the influence of the independent variables used in the model of funding research on policy as the dependent variable of 20.8%.Keywords : Current Ratio, Managerial Ownership, Asset Growth , Company Size, Funding Policy.